Análisis de errores conceptuales en geología a partir de las expresiones gráficas de los estudiantes - Lillo Beviá, José (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
Detection of misconceptions by pupil's drawings permits us to have evidence of some misconceptions wich would have gone unnoticed interpreting only their vocal or writing expressions. Investigation on fossil and fossilisation, internal structure of the Earth, origin of mountains and others, reinforces the previous affirmation and permits us to recommend the non -utilisation of sequential drawings containing high conceptual charge, in order to simplify complex geological processes, because that simplification generates new misconceptions.